2019
DOI: 10.3851/imp3358
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Long-Term ART Exposure: Findings from an Asian Patient Population Retained in Care beyond 5 Years on ART

Abstract: Background: This study investigated survival in people living with HIV being followed-up from 5 and 10 years after antiretroviral therapy (ART) initiation in a multicountry Asian cohort. Methods: We included patients in follow-up >5 years after ART initiation. Factors associated with mortality beyond 5 and 10 years on ART were analysed using competing risk regression with time-updated variables. Results: Of 13,495 patients retained after 5 years on ART, 279 subsequently died (0.56/100 person-years). Increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
2
6
1
Order By: Relevance
“…In our study, hyperglycemia was associated with a more than 2-fold increase in mortality risk. Association between diabetes mellitus and death has been well documented [ 21 ], and our findings add to the body of knowledge showing that hyperglycemia is an independent risk factor for mortality [ 11 , 13 , 22 , 23 ]. Hyperglycemia can indicate missed diagnosis of diabetes mellitus, especially in resource-limited settings where care for non-communicable diseases is rarely integrated into HIV service delivery [ 24 ].…”
Section: Discussionsupporting
confidence: 78%
“…In our study, hyperglycemia was associated with a more than 2-fold increase in mortality risk. Association between diabetes mellitus and death has been well documented [ 21 ], and our findings add to the body of knowledge showing that hyperglycemia is an independent risk factor for mortality [ 11 , 13 , 22 , 23 ]. Hyperglycemia can indicate missed diagnosis of diabetes mellitus, especially in resource-limited settings where care for non-communicable diseases is rarely integrated into HIV service delivery [ 24 ].…”
Section: Discussionsupporting
confidence: 78%
“…Increasing age has been associated with increased mortality among PLHA in previously published studies also. (5)(6)(7) Various studies have shown male gender, lower CD4 counts at initiation of ART and ART regimens using didanosine or abacavir to be associated with unfavourable outcomes. (6-9) In the present study, gender, WHO stage at initiation of ART, CD4 count at initiation of ART, educational and occupational status, marital status, possible mode of HIV infection, delay from HIV diagnosis till ART initiation or the initial ART regimen were not predictive of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 441 adult HIV-positive individual records were reviewed with the median age (IQR) of the respondents was 32 (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years. From the total study participants, more than half (59.86%) were females and nearly two-thirds, 62.36%, of the patients lived in urban areas.…”
Section: Socio-demographic Characteristics Of Patientsmentioning
confidence: 99%